2012
DOI: 10.1073/pnas.1205798110
|View full text |Cite
|
Sign up to set email alerts
|

Single-molecule analysis of fluorescently labeled G-protein–coupled receptors reveals complexes with distinct dynamics and organization

Abstract: G-protein-coupled receptors (GPCRs) constitute the largest family of receptors and major pharmacological targets. Whereas many GPCRs have been shown to form di-/oligomers, the size and stability of such complexes under physiological conditions are largely unknown. Here, we used direct receptor labeling with SNAP-tags and total internal reflection fluorescence microscopy to dynamically monitor single receptors on intact cells and thus compare the spatial arrangement, mobility, and supramolecular organization of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

56
473
6
2

Year Published

2014
2014
2022
2022

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 409 publications
(537 citation statements)
references
References 40 publications
56
473
6
2
Order By: Relevance
“…In the case of the neurotensin NTS 1 dimer, a half-life of 340 s has been observed (White et al, 2007) and evidence has been found that M 1 muscarinic receptor dimers have an estimated half-life of 0.5 s (Hern et al, 2010). In a study by Calebiro et al (2013), β 1 -and β 2 -adrenoceptors were monitored on the surface of living cells and the kinetics of the interactions leading to the formation of oligomers was characterized. All these receptors dynamically formed dimers and high-order oligomers, with an apparent half-life in the order of 4-6 s. Thus, a dynamic equilibrium condition was established at the cell surface, with constant formation and dissociation of new receptor complexes.…”
Section: Quaternary Structure Of Gpcr Complexesmentioning
confidence: 99%
“…In the case of the neurotensin NTS 1 dimer, a half-life of 340 s has been observed (White et al, 2007) and evidence has been found that M 1 muscarinic receptor dimers have an estimated half-life of 0.5 s (Hern et al, 2010). In a study by Calebiro et al (2013), β 1 -and β 2 -adrenoceptors were monitored on the surface of living cells and the kinetics of the interactions leading to the formation of oligomers was characterized. All these receptors dynamically formed dimers and high-order oligomers, with an apparent half-life in the order of 4-6 s. Thus, a dynamic equilibrium condition was established at the cell surface, with constant formation and dissociation of new receptor complexes.…”
Section: Quaternary Structure Of Gpcr Complexesmentioning
confidence: 99%
“…It is known from studies of G-protein-coupled receptors (GPCRs) that an equilibrium may exist between monomers and oligomers (Lambert 2010, Teichmann et al 2012, Calebiro et al 2013, implying that protomer-protomer interfaces are flexible or transient. Amino acid mutations can shift this equilibrium toward a monomeric or more oligomeric state if they modify the interface(s) between the protomers.…”
Section: Transporter Oligomers and Structure-function Relationshipsmentioning
confidence: 99%
“…Single-molecule microscopy has the great potential of directly visualizing with high spatiotemporal resolution the dynamic behavior of individual receptors located on the surface of living cells, including their association to form dimers and higher order molecular complexes [6][7][8][9][10] . This offers several advantages compared to standard biochemical and microscopy methods, which usually report the average behavior of thousands or millions of molecules.…”
Section: Introductionmentioning
confidence: 99%
“…The reported protocol results in >90% labeling efficiency of an extracellularly SNAP-tagged cell-surface protein 10 . Further information on how to use single-molecule data to analyze the size and mobility of receptor complexes, as well as to capture transient receptor-receptor interactions, is provided.…”
mentioning
confidence: 99%
See 1 more Smart Citation